Fenton‒Like Oxidation Of Acid And Reactive Dyes Using Natural‒Materials Supported Catalysts - Daud, Nor Khonisah (2010)
The primary aim of this study was to prepare Fe‒based catalysts for the decolorization of two types of dye as a model of real textile wastewater, Acid Red 1 (AR1) and Reactive Black 5 (RB5). The catalysts were prepared from low‒cost materials and agricultural by‒product abundantly available in Malaysia, namely Montmorillonite K10, granite, kaolin and rice husk ash by impregnation method. Nitrogen adsorption/desorption, Energy Disperse X‒ray (EDX), Scanning Electron Microscope (SEM), Fourier Transform Infrared spectroscopy (FTIR) and X‒ray powder diffraction (XRD) were used to characterize the catalysts. The efficiency of the reaction system was explored as a function of the experimental parameters such as effect of iron (III) oxide loading on the supports, catalyst dosage, pH, hydrogen peroxide concentration, initial dye concentration and reaction temperature. The optimum conditions obtained for decolorization process for both dyes were 0.070‒0.14 wt.% of Fe‒contained supports, 3.50‒5.0 g L‒1 of catalyst dosage, 2.0‒2.50 pH and 8.0‒20 mM of initial concentration of hydrogen peroxide with 50 mg L‒1 of initial dye concentration at 30 oC reaction temperature.